Analysing the potential of telecommuting as a substitute for commute level - Kadar Hamsa, Abdul Azeez; Wan Mohd Rani, Wan Nurul Mardiah (2007)
Earlier research had identified association between telecommuting and commute travel. Telecommuting is considered as a travel demand management measure in mitigating travel especially work trip to the central business district. However, whether it acts as an effective travel demand management measure is still remain to be seen. This paper investigates potential of telecommuting as a travel substitute especially for work related trips. The analysis of travel substitution as a result of practicing telecommuting was made based on stated preference of the employees in the selected business organizations by questionnaire survey. The survey was administered in two major cities namely Kuala Lumpur and Johor Bahru in Malaysia. Work trip components include commute trip and vehicle-km. Telecommuting frequency between 1 and 3 days per week was considered for this study. The analysis revealed that the commute trip reduction from stated preferred telecommuters was not more than 10% of the total commute trips.